The Global Nomad’s Guide to University Transition - Zhang, Yi (Leaf) (Journal of International Students, 2013)
The Global Nomad’s Guide to University Transition (Quick, 2010) is specifically written for third culture kids (TCKs) who will begin their journey into university life. TCKs are defined as those who grew up in places outside of their home or passport cultures and have no sense of belonging in neither the home culture nor host culture. These students usually find their sense of belonging in the third culture, which is the community of people who share the experience of living outside their passport cultures. This book also aims to prepare parents of TCKs to better understand their children’s challenges thus assisting them with a smoother transition to college.